Reidemeister torsion of link complements in a 3-torus - Vuong, Huu Bao (Вестник Томского государственного университета. Математика и механика)
We prove that the Reidemeister torsion and the twisted Alexander polynomial of the complement of a link in a three-dimensional torus are the same.